Chemical Conjugation in Drug Delivery Systems - Alexis Eras; Danna Castillo; Margarita Suárez; Nelson Santiago Vispo; Fernando Albericio; Fernando Albericio; Fernando Albericio; Hortensia Rodriguez (Frontiers in Chemistry, 2022)
Cancer is one of the diseases with the highest mortality rate. Treatments to mitigate cancer are usually so intense and invasive that they weaken the patient to cure as dangerous as the own disease. From some time ago until today, to reduce resistance generated by the constant administration of the drug and improve its pharmacokinetics, scientists have been developing drug delivery system (DDS) technology. DDS platforms aim to maximize the drugs’ effectiveness by directing them to reach the affected area by the disease and, therefore, reduce the potential side effects. Erythrocytes, antibodies, and nanoparticles have been used as carriers. Eleven antibody–drug conjugates (ADCs) involving covalent linkage has been commercialized as a promising cancer treatment in the last years. This review describes the general features and applications of DDS focused on the covalent conjugation system that binds the antibody carrier to the cytotoxic drug.